Proceedings of the 6th International Driving Symposium on Human Factors in Driver Assessment, Training, and Vehicle Design : Dr 2011
DOI: 10.17077/drivingassessment.1382
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cognitive Workload on Physiological Arousal and Performance in Younger and Older Drivers

Abstract: Summary:Two groups, aged 25-35 and 60-69, engaged in 3 levels of a delayed auditory recall task while driving a simulated highway. Heart rate and skin conductance increased with each level of demand, demonstrating that these indices can correctly rank order cognitive workload. Effects were also observed on speed and SD of lane position, but they were subtle, nonlinear, and did not effectively differentiate. Patterns were quite consistent across age groups. These findings on the sensitivity of physiological mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
2
4
0
Order By: Relevance
“…This demonstrates that in addition to detecting marked changes in driving conditions such as entering a traffic circle (Brookhuis & de Waard, 2001) or in secondary task difficulty (i.e., between a 0-back and a 3-back task; Lenneman & Backs, 2009), these measures can discriminate subtle differences across a range of demand levels. A recently completed simulation study by colleagues in Korea (Son et al, 2011), based on this protocol, produced comparable findings on the question of sensitivity, providing further evidence for the generalizability of these results.…”
Section: Comparison Of Sensitivity Of Physiological Visual Attentionsupporting
confidence: 55%
“…This demonstrates that in addition to detecting marked changes in driving conditions such as entering a traffic circle (Brookhuis & de Waard, 2001) or in secondary task difficulty (i.e., between a 0-back and a 3-back task; Lenneman & Backs, 2009), these measures can discriminate subtle differences across a range of demand levels. A recently completed simulation study by colleagues in Korea (Son et al, 2011), based on this protocol, produced comparable findings on the question of sensitivity, providing further evidence for the generalizability of these results.…”
Section: Comparison Of Sensitivity Of Physiological Visual Attentionsupporting
confidence: 55%
“…Heart rate was examined as a driver behavior measure, and found that absolute validity and relative validity were established. The result indicated that heart rate is one of the most useful measures for investigating a driver's cognitive workload for both simulated and real world driving as suggested in previous studies [14,15,16].…”
Section: Discussionsupporting
confidence: 63%
“…Persons differ in the amount of these capabilities which they possess, and their strategies for employing them. (p. 22) In our research on the use of physiological measures in state detection and workload assessment, we generally focus on workload from the perspective of the level of effort or mobilization of resources that appears to be associated with a task or set of conditions [2,13,14,15,19,20,23]. This approach explicitly recognizes that the same level of objectively defined external demand is likely to produce a wide range of effective workload on different individuals depending upon their own capacities, experience, and current emotional state and reactivity.…”
Section: Defining Workloadmentioning
confidence: 99%